Efecto de la temperatura sobre la producción de saccharum officinarum l. variedad México 73-0523 en la Empresa Agroindustrias San Jacinto S.A.A., ANCASH, AÑOS 2011 AL 2013 - Ciriaco Tarazona, Wilber Joaquín (2015)
This report thesis was to analyze the effect of temperature on the production of Saccharumofficinarum L. range 73-0523 Mexico in the company Agroindustrias San Jacinto SAA, Ancash, years 2011 to 2013; for this statistical information obtained from sugar production reports and weather temperature data generated by the weather station Juan Diaz correlated. As a result, and based on statistical test of simple linear regression, we found that the oscillation of temperature is positive, with moderate linear dependence and a significance level of 0.003 below the set (p <0.05) proving that the regression model linear exists but explained 23.7% of the values of sucrose. While it was found that the variables of maximum, minimum and average temperature has a negative or inverse relationship to the performance of cane per hectare (TCH) and sugar yield per hectare (TAH), with strong linear dependence and lower significance level set (p <0.05) indicating that the linear regression model exists, but account for a third of the values of TCH in 36.5%, 34.1% and 36.2% respectively, and explained 12.0%, 13.4% and 12.9% values TAH respectively.